Multidimensional analysis of indigenous bread from the Brazilian Amazon - Brandão, Kelly; Furquim, Laura; Cangussu, Daniel; Strauss, André; Mendes dos Santos, Gilton; Neves, Eduardo Goes; Villagran, Ximena S. (Frontiers in Environmental Archaeology, 2025)
The Indigenous bread of the Amazon is an ancient food technology, with records dating back at least to 1,200 AD. This food technology survived the colonial period and was continuously produced by Amazonian Indigenous people until the 20th century. Accounts of these breads can be found in chronicles, travelers' records, and the oral traditions passed down by forest peoples. Previous studies rejected the oral history of different indigenous peoples and classified bread as a new species of fungus with a large mycelium. Recent research has reshaped this perspective by identifying a diversity of ingredients and production processes. These new insights reveal different recipes incorporating corn, chili pepper, palm fruits, mairá potato, and other tubers, while highlighting techniques such as fermentation and smoking. This study characterizes indigenous bread using a geo and microarchaeological approach including analytical imaging methods (petrography, stereoscopic mosaic, and micro-computed tomography–micro-CT), which were combined with Fourier-transform infrared spectroscopy (FTIR). Multidimensional analyses identified two distinct bread microstructures: massive and spongy. Additionally, specific manufacturing characteristics were detailed, such as wrapping the bread in organic matter (e.g., leaves), for the massive bread, and in clay, for the spongy bread. Smoking was also used to create a hardened crust on the surface while preserving a soft interior. Analyses also revealed that massive bread contains clay, and clay consumption has been widely described in travelers' accounts and oral traditions in the Amazon. This study contributes to the efforts of archaeobotanical research in understanding the ancient food technology of Amazonian people.